Controlled formation of core–shell structures with uniform AlPO4 nanoshells. Issue 14 (14th January 2015) - Yang, Fen-Li; Zhang, Wei; Chi, Zi-Xiang; Cheng, Fu-Quan; Chen, Ji-Tao; Cao, An-Min; Wan, Li-Jun
Abstract : Uniform AlPO4 nanoshells are successfully achieved on different core materials by controlling their formation kinetics in solution. Abstract : Uniform AlPO4 nanoshells are successfully achieved on different core materials by controlling their formation kinetics in solution. The application of this coating protocol to LiCoO2 shows an obvious improvement in its battery performance.